EVALUASI KENYAMANAN FISIK RUANG KELAS DAN PERPUSTAKAAN SEKOLAH DASAR DI KOTA MALANG - Istiqomah, Annisa Widhi; Ichwanto, Muhammad Aris; Nisa, Aqeela Zahratun; Syahrifah, Aqilah Auliana; Rahayu, Ariffa; Kiong, Tee Tze (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The quality of the school's physical environment, specifically lighting and acoustics, is a primary determinant influencing learning comfort and students' psychological health. However, many elementary school buildings in Malang City still face technical constraints due to suboptimal architectural planning. This study aims to evaluate the effectiveness of classroom and library performance against functional comfort standards. The method employed is quantitative descriptive through field observations and direct measurements in two rooms, each with dimensions of 8 x 8 meters. The data collection procedure implemented a grid sampling technique, consisting of 32 measurement points (Grid A-H) in the classroom and 49 measurement points (Grid A-G) in the library. The results indicate a significant natural lighting deficit, with average light intensities in the classroom (56.0–65.0 Lux) and the library (49.5–59.9 Lux) falling far below the minimum standard of 300 Lux (SNI 03-6197-2000). This is triggered by the suboptimal use of passive elements (glass blocks and boventlights) and building facade obstructions. Meanwhile, the acoustic aspect consistently exceeds the ideal threshold of 55 dB (SNI 7231:2009), with peak noise reaching 65.6 dB in the library due to fundamental master plan errors that placed the literacy area adjacent to the cafeteria. These conditions increase the cognitive load and the risk of visual fatigue for students. This study recommends the optimization of artificial lighting and the installation of sound absorbers to create a learning environment that is higher in quality, standardized, and inclusive.